The Influence of Perception of Ease, Usefulness, Enjoyment, and Interaction on User Satisfaction and Purchase Intention Through the Chatbot “Tanya” on the Tokopedia Platform - Raihanatul Jennah; Arif Hartono (Universitas KH. Abdul Chalim Mojokerto, 2025)
The rapid growth of digital technology has accelerated the use of artificial intelligence in customer service, particularly through chatbots on e-commerce platforms. This study examines the effects of Perceived Ease of Use, Perceived Usefulness, Perceived Enjoyment, and Interaction on user Satisfaction, as well as their influence on Purchase Intention, with a focus on Tokopedia's